Active Vibration Control Strategy for Online Application in a Range Extender - Zhang Jinyu; Hu Song; Ju Longyu; Yang Fuyuan (IEEE Access, 2023)
Noise, vibration and harshness are a big issue for hybrid vehicles especially in range extenders. Traditional vibration control and active damping control are generally used for suppressing vibration. Compared with traditional vibration control, active damping control is more flexible and effective in suppressing vibration. The basic idea of active damping control is controlling electric motor compensating for the torque of engine and reducing the vibration from the source. The reduction of vibration is highly depended on the compensation torque of the electric motor. A differently designed compensation torque has a significant impact on the active damping control effect. In this paper, an active damping control method for online application is proposed. And several kinds of compensation torque are designed for this method. Experiments on vibration performance are conducted to compare the effect of different compensation torque design in reducing vibration. And the results show that the compensation torque in the shape of square wave has potential for reducing vibration in all directions. Finally, a guiding tool for compensation design is proposed by correlation analysis and the relationship between designing factors and vibration is revealed.